2018
DOI: 10.1001/jamainternmed.2017.6299
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Care Eligibility, Symptom Burden, and Quality-of-Life Ratings in Nursing Home Residents

Abstract: By 2030, it is projected that 40% of all US deaths will occur in nursing homes (NHs). 1 Despite an estimated $136 billion spent each year, NH care has been associated with poor symptom control, low family satisfaction, and burdensome and unnecessary care transitions in the final months of life. [1][2][3] Little is known about this vulnerable population's specific palliative care (PC) needs. As part of a PC quality initiative, we sought to identify which NH residents were eligible for PC services, describe the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 5 publications
0
28
0
Order By: Relevance
“…The literature consulted shows that identification of the terminal state increases the likelihood of a de-prescription occurring [34]. In the case of nursing homes, this identification is critical for facilitating patients' access to palliative care and, consequently, for improving the quality of care they receive, their satisfaction with it, and their symptoms [35]. Our results may be due to the lack of use of predictive survival tools that could be used in these centres.…”
Section: Discussionmentioning
confidence: 92%
“…The literature consulted shows that identification of the terminal state increases the likelihood of a de-prescription occurring [34]. In the case of nursing homes, this identification is critical for facilitating patients' access to palliative care and, consequently, for improving the quality of care they receive, their satisfaction with it, and their symptoms [35]. Our results may be due to the lack of use of predictive survival tools that could be used in these centres.…”
Section: Discussionmentioning
confidence: 92%
“…In the United States, a recent study identified that 69% of care home residents were eligible for palliative care but weren't receiving any. (Stephens et al, 2018) Care homes are often confused about the roles of external providers which leads to poor coordination of care and a delay in receiving services (Gage et al, 2016) There is also evidence that symptoms at the end of life in care homes are poorly managed. A study from the Netherlands indicates approximately 43% of nursing home residents have pain with this number increasing in residents with vascular dementia to 54%.…”
Section: Introductionmentioning
confidence: 99%
“…23 Integrating consultative palliative care services into primary care, nursing home settings, and other models of care— such as home-based primary care—may also improve pain management and reduce ED use at the end-of- life for older adults with dementia. 2426 For example, early palliative care consults with nursing home residents with dementia was associated with an almost 12% reduction in ED visits in the last 30 days of life. 24 However, palliative care for people with dementia is in early stages of development, and more work is needed to develop palliative care models and programs tailored to the unique needs of people with dementia near the end-of-life.…”
Section: Discussionmentioning
confidence: 99%